Intraoperative pelvic neuromonitoring based on bioimpedance signals: a new method analyzed on 30 patients - Kalev, Georgi; Schuler, Ramona; Langer, Andreas; Goos, Matthias; Konschake, Marko; Schiedeck, Thomas; Marquardt, Christoph (Langenbeck's archives of surgery, 2024)
Purpose Increasing importance has been attributed in recent years to the preservation of the pelvic autonomic nerves during rectal resection to achieve better functional results. In addition to improved surgical techniques, intraoperative neuromonitoring may be useful. Methods This single-arm prospective study included 30 patients who underwent rectal resection performed with intraoperative neuromonitoring by recording the change in the tissue impedance of the urinary bladder and rectum after stimulation of the pelvic autonomic nerves. The International Prostate Symptom Score, the post-void residual urine volume and the Low Anterior Resection Syndrome Score (LARS score) were assessed during the 12-month follow-up period. Results A stimulation-induced change in tissue impedance was observed in 28/30 patients (93.3%). In the presence of risk factors such as low anastomosis, neoadjuvant radiotherapy and a deviation stoma, an average increase of the LARS score by 9 points was observed 12 months after surgery (p = 0,04). The function of the urinary bladder remained unaffected in the first week (p = 0,7) as well as 12 months after the procedure (p = 0,93). Conclusion The clinical feasibility of the new method for pelvic intraoperative neuromonitoring could be verified. The benefits of intraoperative pelvic neuromonitoring were particularly evident in difficult intraoperative situations with challenging visualization of the pelvic nerves.
Gesehen am 25.02.2025